2019
DOI: 10.1021/acs.iecr.9b01941
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Applications of Diatomite Minerals in Removing Heavy Metals from Water

Abstract: Heavy metals released into the environment could accumulate in living organisms, thus causing various diseases and disorders. Diatomite, an eco-environmental functional material, has been proved to be a very promising and effective adsorbent in heavy metal-contaminated water treatment because of its high porosity, low density, high specific surface area, and surface silanol groups. This review (i) describes the characteristics, advantages, and limitations of diatomite; (ii) presents the capability of heavy met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 113 publications
1
30
0
Order By: Relevance
“…They both have molecular-level micro-pores, with uniform pore size distributions. [42][43][44] It was found that the zeolite and diatomite had a relatively higher adsorption capacity for AF, indicating they had higher combining ability with the triarylmethane dyes possessing medium molecular dimensions and stronger polarity. Activated carbon is amorphous carbon based on a graphite structure, with developed porosity, high specic surface and a certain amount of oxygen-containing groups.…”
Section: Adsorption Studiesmentioning
confidence: 99%
“…They both have molecular-level micro-pores, with uniform pore size distributions. [42][43][44] It was found that the zeolite and diatomite had a relatively higher adsorption capacity for AF, indicating they had higher combining ability with the triarylmethane dyes possessing medium molecular dimensions and stronger polarity. Activated carbon is amorphous carbon based on a graphite structure, with developed porosity, high specic surface and a certain amount of oxygen-containing groups.…”
Section: Adsorption Studiesmentioning
confidence: 99%
“…34 The resulting structure is responsible for diatomite physical-chemical properties like high surface area, thermal stability, and good chemical and mechanical resistance. 35 The abundance, low-price, and unique properties of this material are the reasons why diatomite has been widely used in many technical fields including thermal insulation, 36 constructions, catalysis, filters, hazardous waste absorption, 37 paint fillers, and insecticide. 38 Herein, we studied the cold sintering process of diatomaceous earth aiming at (i) pointing out the applicability of CSP to such material, (ii) understanding the effect of the main process conditions (pressure, temperature, liquid solution composition) on densification, and (iii) identifying the microstructural features of the CSP material.…”
Section: Introductionmentioning
confidence: 99%
“…Diatomite is a highly porous compound with excellent chemical stability and hydrophilicity [26], and it has received approval as a food-grade material from the US Food and Drug Administration [27]. Previous studies have explored the successful use of diatomite for the safe and effective treatment of water and wastewater supplies owing as its ability to function as an adsorbent or a flocculant [28][29][30][31]. Given its high porosity and the fact that it is denser than water, diatomite has the potential to be ideally suited to serving as a GO flocculant aid.…”
Section: Introductionmentioning
confidence: 99%